ANALISIS PENGARUH SAFETY CULTURE TERHADAP KEPATUHAN PENGGUNAAN APD PADA PEMBANGUNAN RUMAH SAKIT XYZ - Marini Grace Gultom; Erida Denyaty Tambunan; Fachreza Solahuddin Ritonga; Refael Markus Samosir; Edo Barlian; A.Daniel Anderson Munthe (Universitas Muhammadiyah Metro, 2026)
This study examined the influence of workplace safety culture on workers' compliance with personal protective equipment (PPE) usage at the XYZ Hospital construction project over a four-week observation period in April 2026. The findings demonstrate a consistent and progressive improvement in PPE compliance, which can be attributed to structured safety culture reinforcement measures implemented throughout the observation period. During the first week (April 6–11, 2026), average PPE compliance rates ranged between 86–88%. While this figure already reflects a relatively high baseline level of compliance, instances of non-compliance were still recorded, particularly regarding the use of gloves and safety vests. This suggests that, at the outset, workers had general awareness of PPE requirements, but adherence to all four types of equipment — helmets, safety vests, safety shoes, and gloves — was not yet fully consistent. A notable upward trend emerged in the second and third weeks, as compliance rates climbed to 90–96%. This improvement coincided with the implementation of daily morning safety briefings (K3 briefings), intensified safety socialization sessions, and stricter supervision by the project management team. These findings are consistent with the view that safety culture is not merely a static set of rules but an active, ongoing process shaped by managerial engagement and continuous communication. When workers receive regular reminders and perceive that management genuinely prioritizes safety, their behavioral compliance tends to increase accordingly. By the fourth week (April 24–30, 2026), PPE compliance reached its highest recorded levels, ranging from 94–98%, with an overall average of 91.6% across the entire observation period. This peak level of compliance, sustained toward the end of the study, suggests that the safety interventions did not produce only a short-term or reactive effect, but contributed to a gradual normalization of safe behavior among the workforce. A particularly noteworthy finding is that compliance improvements were sustained despite daily variation in the number of workers on site. This indicates that the behavioral changes observed were not simply a function of workforce size or composition on any given day, but were instead driven by shifts in workplace safety culture — specifically, through the combined influence of routine supervision, continuous socialization, and active managerial support. This distinction is important, as it points to culture and management as more reliable predictors of compliance than situational or demographic factors. These results align with the broader literature on safety climate and behavioral safety, which consistently identifies management commitment, worker involvement, and communication as key determinants of safety compliance in high-risk industries. The construction sector, with its dynamic work environments, rotating workforce, and multi-hazard conditions, is particularly dependent on strong safety culture as a foundation for consistent protective behavior. From a practical standpoint, this study underscores the importance of embedding safety culture reinforcement into daily project management routines, rather than treating safety briefings or socialization as one-time events. The progressive improvement observed here suggests that frequency and consistency of safety communication — combined with visible management accountability — are critical levers for sustaining and improving PPE compliance over time. This research is expected to serve as a practical reference for contractors and project managers, particularly those involved in the construction of healthcare facilities, where safety failures carry heightened consequences for both workers and future patients. Developing and enforcing a structured safety culture framework — encompassing regular oversight, participatory safety briefings, and sustained managerial engagement — appears to be an effective strategy for improving worker discipline and reducing PPE non-compliance in construction project environments.